Caveolin-1 Deficiency Protects Mice Against Carbon Tetrachloride-Induced Acute Liver Injury Through Regulating Polarization of Hepatic Macrophages - Yang, Ziheng; Zhang, Jie; Wang, Yan; Lu, Jing; Sun, Quan (Frontiers in Immunology, 2021)
Polarization of hepatic macrophages plays a crucial role in the injury and repair processes of acute and chronic liver diseases. However, the underlying molecular mechanisms remain elusive. Caveolin-1 (Cav1) is the structural protein of caveolae, the invaginations of the plasma membrane. It has distinct functions in regulating hepatitis, cirrhosis, and hepatocarcinogenesis. Given the increasing number of cases of liver cancer, nonalcoholic steatohepatitis, and non-alcoholic fatty liver disease worldwide, investigations on the role of Cav1 in liver diseases are warranted. In this study, we aimed to investigate the role of Cav1 in the pathogenesis of acute liver injury. Wild-type (WT) and Cav1 knockout (KO) mice (Cav1tm1Mls) were injected with carbon tetrachloride (CCl4). Cav1 KO mice showed significantly reduced degeneration, necrosis, and apoptosis of hepatocytes and decreased level of alanine transaminase (ALT) compared to WT mice. Moreover, Cav1 was required for the recruitment of hepatic macrophages. The analysis of the mRNA levels of CD86, tumor necrosis factor (TNF), and interleukin (IL)-6, as well as the protein expression of inducible nitric oxide synthase (iNOS), indicated that Cav1 deficiency inhibited the polarization of hepatic macrophages towards the M1 phenotype in the injured liver. Consistent with in vivo results, the expressions of CD86, TNF, IL-6, and iNOS were significantly downregulated in Cav1 KO macrophages. Also, fluorescence-activated cell sorting (FACS) analysis showed that the proportion of M1 macrophages was significantly decreased in the liver tissues obtained from Cav1 KO mice following CCl4 treatment. In summary, our results showed that Cav1 deficiency protected mice against CCl4-induced acute liver injury by regulating polarization of hepatic macrophages. We provided direct genetic evidence that Cav1 expressed in hepatic macrophages contributed to the pathogenesis of acute liver injury by regulating the polarization of hepatic macrophages towards the M1 phenotype. These findings suggest that Cav1 expressed in macrophages may represent a potential therapeutic target for acute liver injury.